Hemostatic parameters in pulmonary tuberculosis patients after intensive phase treatment - Lingga Suryakusumah; Nur Ahmad Tabri; Sahyuddin Saleh; Syakib Bakri; Hasyim Kasim; Andi Fachruddin Benyamin; Erwin Arief; Arifin Seweng (Babol University of Medical Sciences, 2021)
Background: Tuberculosis (TB) is an infectious disease caused by mycobacterium tuberculosis (Mtb). This infection causes the release of proinflammatory cytokines that affect hemostasis. Pulmonary TB infection causes an increased activation of procoagulant factors, decreased anticoagulant factors and suppresses fibrinolysis which causes hypercoagulable. Our study is conducted to assess the association between pulmonary TB infection (PTB) with hemostatic parameters before and after intensive phase treatment. Methods: This was an analytic observational prospective cohort design. The study was conducted at the Community Center for Lung Health in South Sulawesi. Studied subjects were recruited by consecutive sampling, in which the patients who met the inclusion criteria received intensive phase of ATD treatment. PT, aPTT, fibrinogen, and D-dimer were measured before treatment and after the intensive phase of ATD. These data were analyzed using the SPSS Version 22. Results: In this study, 30 subjects are new cases of PTB. Prothrombin time, aPTT and D-dimer levels were higher in far advanced lesions and smear-positive sputum group (p<0.001). There was a significant level decrease in PT, aPTT, fibrinogen, D-dimer after intensive phase treatment (p<0.001). Conclusion: Pulmonary tuberculosis infection is associated with hypercoagulability which is characterized by an increase in hemostatic parameters and has significant improvement after intensive phase of ATD treatment.